Implementation of Nasogastric Tube Feedings at Discharge in a Large Quaternary NICU: A Literature Review, Proposed Algorithm, and Our Center Experience - Ibrahim, John; Azzuqa, Abeer; Kloesz, Jennifer; Balest, Arcangela (American Journal of Perinatology, 2025)
The aim of this study is to provide an extensive review of the published literature regarding the use of nasogastric (NG) feeds at discharge in the neonatal population as well as our experience with the implementation of an NG feeds at discharge program in our level IV neonatal intensive care unit.We reviewed and compared the use of NG tubes at discharge and gastrostomy tubes in the neonatal population. We provide an extensive review of previous publications regarding programs of NG feeds at discharge in neonates across the United States and Europe including preterm neonates, neonates with chronic lung disease, and neurological injury. We also reviewed parents' perspectives on NG use at discharge in the neonatal population as well as the use of telehealth in remote monitoring of neonates discharged on NG feeds. We reviewed the economic benefits of such programs. We finally provide our center's algorithm and workflow as well as our center's experience.Twenty-five patients have been discharged so far from this program since its implementation in December 2020. Only 1 patient of the 25 patients discharged on NG tube feeds required gastrostomy tube placement.Discharge with NG tube feeds in a carefully selected population is safe, and feasible and can lead to increased parent satisfaction, besides offering a developmental advantage for the neonates when the only remaining inpatient need is achieving full oral feeds.
Keywords: neonates; nasogastric feeds at discharge; oral feeding; nutrition; premature neonates; bronchopulmonary dysplasia; telehealth